In The Shadow of the Freakshow: The Impact of Freakshow Tradition on the Display and Understanding of Disability History in Museums - Richard Sandell; Annie Delin; Jocelyn Dodd; Jackie Gay (Disability Studies Quarterly, 2005)
In 2003 a research project was undertaken by The Research Centre for Museums and Galleries (RCMG), Department of Museum Studies, University of Leicester. Buried in the Footnotes set out to address a deficit in knowledge and understanding around the hidden history of disability by investigating museum collections and displays in the UK to identify evidence attesting to the lives of disabled people. The project further aimed to identify and examine curatorial practices and other factors, which may have contributed to historical and contemporary under- or mis-representation of disabled people, including through the examination of how information associated with disabled people comes to be changed, distorted or lost. In this essay, the research team presents elements of the research findings relating to freak material, artifacts and records. We report on the material identified, examine the responses and attitudes of museum curators to holding and showing such material, and consider the impact of curatorial perspectives on the record and display of disability history.
Keywords: freaks; museums; curatorial practice; disability history; anthropology; Charles Stratton (Tom Thumb); Arthur Caley (The Manx Giant); Joseph Merrick (The Elephant Man); Sarah Biffin; John Vine.